Multiple Faces of Posted Workers Process: A Survey Carried out on Firms, from Romania, that Posted Workers - Elena HLACIUC; Daniel RATA; Romania (Communications of International Proceedings, 2022)
The main objective of the research carried out was to study the perception of economic entities, in the field of construction and transport, about the impact of accounting and taxation over the process of posting workers, as well as measuring the degree to which they consider that accounting policies influence this process. The perceptions of multiple faces of posting workers is necessary because mistakes occur as a result of the complexity of tax systems, and tax authorities should not automatically assume that any non-compliance is deliberate and fraudulent. Both, a good understanding, in terms of process or accounting rules, of posting of workers and  correct calculation involves clear rules, which is not happening, at the time of this research, in the field of human resource mobility in the European Union. So, for study the faces of posting, the main instrument used in our research are the questionnaire. Based on the 141 responses, collected for the 52 questions regarding: posting, accounting and financial policies, opinions about the importance of posting policies on the efficiency of the activity, we succeed to determinate at least three faces of posting: posting as a process, accounting face of posting and tax side of posting of workers. These are the main aspects witch both, the accounting profession and the administrators, must consider in order not to be accused of fraud or tax evasion.
Keywords: posted workers; accounting policies; taxation policies